Longitudinal Study of Untreated Chemical Diabetes. Issue 5945 (14th December 1974) - Logie, A. W.; Stowers, J. M.; Dingwall-Fordyce, I.
Abstract : More information is needed about the "natural history" of early diabetes mellitus. A report is presented of the progress over one to nine years of 72 patients who formed the control group of a clinical trial of chlorpropamide and placebo in the management of subclinical diabetes. Most patients showed no deterioration of carbohydrate tolerance, and only four (5·6%) progressed to overt diabetes. The findings of other published series are reviewed. Studies of the effect of treatment of early diabetes must be large scale and long term, and an untreated control group must be included to prevent apparent improvement in carbohydrate tolerance being wrongly attributed to the effect of therapy.